SISTEM INFORMASI KULIAH KERJA NYATA (KKN) BERBASIS ANDROID UNIVERSITAS LAMPUNG - Syah, Firman; Lukito, Wisnu; Aristoteles, Aristoteles; Efendi, Nur; Eka Febriansyah, Febi (Universitas Lampung, 2018)
Kuliah Kerja Nyata (KKN) is an University of Lampung intracurricular activity, that not only involving college student, but lecturer themselves as an field supervisor. Along with the advances of technology, Badan Pelaksana Kuliah Kerja Nyata (BP-KKN) necessarily need developing an android based information system, in order to giving practiculary easy and more efficient access towards the information. The purpose of this research is developing an KKN information system based on android for college student, field supervisor coordinator lecturer and field supervisor lecturer.Â The system research development is using Incremental method, system development method is based on the software need that divided by three stages that are: requirement analysis, specification and design architecture. Those stages must finished and vitrificated first before continuing to the next stage.Â The research produce an KKN information system based on android that applied into smartphones. The conclusion that obtained from this research is successfully build and developed information system that hopefully helping the college student and field advisor lecturer performing an activity that based on information system in the field. This case also strengthened by the result of questionnaire that got very good respond from both college student and field supervisor lecturer.Â Keywords: Android, College Student, Field Supervisor, KKN, Lecturer, Unila